2012
DOI: 10.2134/jeq2011.0077
|View full text |Cite
|
Sign up to set email alerts
|

Capacity of Biochar Application to Maintain Energy Crop Productivity: Soil Chemistry, Sorghum Growth, and Runoff Water Quality Effects

Abstract: Pyrolysis of crop biomass generates a by-product, biochar, which can be recycled to sustain nutrient and organic C concentrations in biomass production fields. We evaluated effects of biochar rate and application method on soil properties, nutrient balance, biomass production, and water quality. Three replications of eight sorghum [ (L.) Moench] treatments were installed in box lysimeters under greenhouse conditions. Treatments comprised increasing rates (0, 1.5, and 3.0 Mg ha) of topdressed or incorporated bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 34 publications
3
22
0
3
Order By: Relevance
“…As with Zn and Mn, P must have been slightly available in the biochar. This finding supports previous research indicating that biochar-borne P can contribute to plant-available nutrient forms (Schnell et al, 2012;Ippolito et al, 2012b). As with Zn and Mn, the P content decreased over time for the 0%, 1%, and 2% biochar application rates likely due to mineral forms becoming less available.…”
Section: Soil Ph and Plant-available Nutrientssupporting
confidence: 90%
“…As with Zn and Mn, P must have been slightly available in the biochar. This finding supports previous research indicating that biochar-borne P can contribute to plant-available nutrient forms (Schnell et al, 2012;Ippolito et al, 2012b). As with Zn and Mn, the P content decreased over time for the 0%, 1%, and 2% biochar application rates likely due to mineral forms becoming less available.…”
Section: Soil Ph and Plant-available Nutrientssupporting
confidence: 90%
“…Hass et al (2012) noted that biochar application increased leachate PO 4 concentrations compared to controls, suggesting that chicken manure biochar applications may be limited by environmental P concerns. Similarly, Schnell et al (2012) found that topdressing up to 3 Mg of sorghum‐derived biochar per hectare (with no incorporation) on an eastern Texas Alfisol caused significant surface runoff P losses compared with control soils and that incorporating the biochar into soil reduced runoff P losses by 78%.…”
Section: Biochar Use and Soil Nutrient Dynamicsmentioning
confidence: 93%
“…Surface‐applied biochar without soil incorporation is subject to erosion losses and thus is typically a nutrient source to runoff water. As an example, Schnell et al (2012) found that sorghum [ Sorghum bicolor (L.) Moench] biochar applied at 1.5 and 3.0 Mg ha −1 , especially when topdressed, increased losses of total P and dissolved P in runoff because P in biochar was soluble. Incorporation of biochar into the soil and selection of biochar with high nutrient adsorption capacity can be strategies to reduce nutrient losses in runoff.…”
Section: Impacts Of Biochar Application On Water Erosionmentioning
confidence: 99%